Pemakaian Bahasa Indonesia Pada Iklan Shopee - Nazda Fatimah; Nasywa Syakira Naila; Mutia Aan Ariany (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research reveals that the use of Indonesian in Shopee advertising is a relevant strategy and has a positive impact. The accuracy of linguistic context is the main focus, reflecting wise policies in capturing linguistic diversity in Indonesia. Understanding dialects, phrases and linguistic norms in each region is the main key in creating appropriate and relevant messages. Shopee succeeded in tailoring messages well, in depth, and connecting with consumers from various walks of life, creating significant personal closeness. Language diversity in Indonesia is recognized as the key to success, ensuring that Shopee advertising is not only a marketing effort, but also an authentic communication that is close to consumers' daily lives. Linguistic creativity is an important factor in attracting consumer attention. Puns, local humor and creative expressions create marketing messages that are interesting, entertaining and different from competitors. This creativity is not only a sweetening element, but also an effective strategy in building a positive, attractive and educational brand image. Shopee has successfully utilized Indonesian creatively, not only as a shopping platform, but also as a provider of entertaining and attention-grabbing content. This relevance is not just a communication tool, but also the foundation for building deep and meaningful relationships with consumers in diverse markets. This research highlights that Indonesian is not just words, but a force that can shape feelings, win the hearts of consumers, and create a positive impact in the world of e-commerce.